2016
DOI: 10.1111/ajt.13616
|View full text |Cite
|
Sign up to set email alerts
|

Economic Impacts of ABO-Incompatible Live Donor Kidney Transplantation: A National Study of Medicare-Insured Recipients

Abstract: The infrequent use ABO incompatible (ABOi) kidney transplantation in the US may reflect concern about the costs of necessary preconditioning and post-transplant care. Medicare data for 26,500 live donor kidney transplant recipients (2000 to March 2011), including 271 ABOi and 62 A2-incompatilbe (A2i) recipients, were analyzed to assess pre-transplant, transplant episode, and 3 year post-transplant cost impacts. The marginal costs of ABOi and A2i vs. ABO compatible transplant (ABOc) were quantified by multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 28 publications
(42 reference statements)
0
28
0
Order By: Relevance
“…Previous reports demonstrated that ABO-ILKT is more cost-effective than ABO-CLKT. 9,19,21 The data obtained from the US national cohort study of ILDKT showed that ABO-ILKT was associated with higher Medicare payments and greater outlier payments. One reported to have higher complication rate, especially infectious adverse events, than ABO-CLKT.…”
Section: However Abo-ilkt Remains Much Less Common In the Unitedmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports demonstrated that ABO-ILKT is more cost-effective than ABO-CLKT. 9,19,21 The data obtained from the US national cohort study of ILDKT showed that ABO-ILKT was associated with higher Medicare payments and greater outlier payments. One reported to have higher complication rate, especially infectious adverse events, than ABO-CLKT.…”
Section: However Abo-ilkt Remains Much Less Common In the Unitedmentioning
confidence: 99%
“…6,7 The frequency of the patients who underwent ABO-ILKT in 2015 represents 1.3% of all US LKTs, 8 as ABO-ILKT recipients experience significantly more expensive in pre-transplant, transplant event, and post-transplant costs than ABO-CLKT recipients. 9 Moreover, ABO-ILKT recipients appeared more likely to experience complications, such as wound infection, pneumonia, and urinary tract infection, than ABO-CLKT recipients. 10 In this study, we compared the clinical outcomes, complications, and medical costs at 2 years post-transplantation between ABO-ILKTs and ABO-CLKTs.…”
mentioning
confidence: 99%
“…Accordingly, much attention has been given to expanding the availability of the kidney donor pool. Both patient and graft survival are better for patients who receive a kidney from a living donor . Many patients who are willing living donors are excluded from donation for one reason or another; a history of malignancy is one such exclusion.…”
Section: Introductionmentioning
confidence: 99%
“…42 Our study also has limitations. [67][68][69][70][71] In conclusion, our findings suggest that lymphocyte-depleting induction agents are not associated with a higher risks of CVE in KT recipients. This includes prolonged lymphopenia.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, we restricted our analysis to recipients who used Medicare as their primary insurance from at least 365 days before the date of transplant, although this might affect generalizability, Medicare primary recipients comprise half of the entire KT recipient population in the United States and have historically been considered representative. [67][68][69][70][71] In conclusion, our findings suggest that lymphocyte-depleting induction agents are not associated with a higher risks of CVE in KT recipients. However, in a certain subset of patients ATG use is associated with lower risk of CVE.…”
Section: Discussionmentioning
confidence: 50%